Foxtail Millet - Hariprasanna, K.; Rajendrakumar, P.; Vetriventhan, Mani; Narasimhulu, R.; Parashuram, P. (Springer, 2025)
Foxtail millet, a self-pollinating short-duration cereal, is one of the oldest cultivated millets in the world, which has originated in China, and its main centre of diversity is East Asia, including China and Japan. From Central Asia, it spread to India and European countries and currently is adapted to a wide range of elevations and environmental conditions. China and India are two major foxtail millet-producing countries for grain purpose, though cultivated area has come down drastically in the recent years. Considerable genetic diversity is present within the cultivated germplasm of foxtail millet. Globally, over 46,000 accessions of foxtail millet have been conserved in the genebanks. China has the largest collection of more than 26,000 accessions, followed by India with over 4600 accessions. ICRISAT genebank conserves a global collection of 1542 foxtail millet accessions from 26 countries. The Indian germplasm exploration has covered almost all the states, but further collections have to be planned from western and eastern states where rich diversity exists. In spite of availability of good genetic variability, the use of germplasm in crop improvement is limited due to difficulties in crossing and obtaining the hybrids. Germplasm representative subsets have been developed along with identification of trait-specific genotypes for agronomic traits, tolerance to biotic and abiotic stress and nutritional parameters for enhanced use in breeding programme. Availability of genomic sequence and large quantum of genomic resources is an advantage in foxtail millet compared to other millets. Use of trait-specific germplasm in recombination breeding with refined crossing techniques and deployment of genomic resources in crop improvement will lead to enhanced genetic gains in foxtail millet in future.